A desktop guide for nonprofit directors, officers, and advisors : - Siegel, Jack B. (John Wiley & Sons, 2006)
This guide is an invaluable resource for directors, officers, and advisors to nonprofit organizations. It provides a comprehensive overview of the basic legal, accounting, and financial issues that must be dealt with when governing a nonprofit organization. In an accessible format, it covers a wide range of operational issues, including taxes, insurance, investing money, record retention, director and officer legal duties, accounting, state registration requirements, and more. Appropriate for all types of nonprofit organizations, A Desktop Guide for Nonprofit Directors, Officers, and Advisors cites social service agencies, schools, religious organizations, arts groups and museums, and foundations in a variety of examples.